Desarrollo de estrategias cognitivas de comprensión lectora mediante la herramienta tecnológica nearpod en el área de lengua y literatura del 8 año de educación básica paralelo “A“ de la unidad educativa Roberto Alfredo Arregui Chauvin, Guaranda, Bolívar en el periodo lectivo 2021 – 2022. - Inlago Cuascota, Sonia Lizbeth (2022)
The present project "Development of cognitive reading comprehension strategies through the Nearpod technological tool in the area of Language and Literature aims to improve reading comprehension, for which playful activities were carried out, which help develop reading comprehension skills in students. , in addition to motivating the use of innovative, dynamic strategies, by the educator that strengthens satisfaction with reading, which is essential at the time of the reading process of the eighth "A" students of the Roberto Alfredo Arregui Chauvin Educational Unit, Guaranda, Bolivar.